Study on Effect of Consumer Age, Family Income and Family Size on Fast Fashion Consumption Pattern - Sushil Kumar Bishnoi; Ramratan Guru (Tekstilec, 2023)
The aim of the study was to analyse the impact of various consumer attributes on the fast fashion consumption pattern. The effect of consumer age, family income and family size on the percentage of monthly income spent on clothing and percentage of monthly clothing consumption spent on fast fashion by consumers in NCR (National Capital Region) of India was studied in this research. Causal research was employed in this study. Correlations among the variables were established using the response surface methodology (Box-Behnken experimental design) to understand whether the impact is significant or not. Control factors, studied at 3 levels of variation, were age, monthly family income and family size. The responses for the experiment were the percentage of monthly income (per person) spent on clothing and the percentage of monthly clothing consumption spent on fast fashion. The study revealed that age and monthly family income have a strong influence on the percentage of monthly income spent on clothing, while family size has a negligible or no effect on the percentage of monthly income spent on clothing. It was also found that age, monthly family income and family size have a strong influence on the percentage of monthly clothing consumption spent on fast fashion. The demand for fast fashion and clothing is rising at a very high rate, which has made it hard for retail brands and apparel manufacturers to meet the consumer expectations. The analysis of consumer behaviour provides the advantage to fashion brands in anticipating and meeting consumer demands in a more efficient manner to create brand loyalty.